2023
DOI: 10.1101/2023.01.30.526212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coregulation of extracellular vesicle production and fluconazole susceptibility inCryptococcus neoformans

Abstract: Resistance to fluconazole (FLC), the most widely used antifungal drug, is typically achieved by altering the azole drug target and/or drug efflux pumps. Recent reports have suggested a link between vesicular trafficking and antifungal resistance. Here, we identified novel Cryptococcus neoformans regulators of extracellular vesicle (EV) biogenesis that impact FLC resistance. In particular, the transcription factor Hap2 does not affect the expression of the drug target or efflux pumps, yet it impacts the cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Besides, the H/CA ribonucleoprotein complex subunit 3, Nop10 (CNAG_01049) was found in our EV proteomic analysis (Rizzo et al 2023) which is in agreement with an active targeting of some snoRNAs to EVs. Our research also confirmed the very poor conservation of snoRNA sequences in fungi.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Besides, the H/CA ribonucleoprotein complex subunit 3, Nop10 (CNAG_01049) was found in our EV proteomic analysis (Rizzo et al 2023) which is in agreement with an active targeting of some snoRNAs to EVs. Our research also confirmed the very poor conservation of snoRNA sequences in fungi.…”
Section: Discussionsupporting
confidence: 88%
“…Reads were then aligned to the C. neoformans H99 reference genome (Janbon et al 2014) and the number of reads aligned to each annotated feature was counted (Wallace et al 2020). We used this counting to compare the mRNA and lncRNA abundances in EVs and in cells producing these EVs (Rizzo et al 2023). Our analysis did not reveal spectacular enrichment of any mRNA in EVs (Figure 6).…”
Section: Polya Rnas In Evsmentioning
confidence: 96%
See 3 more Smart Citations